Florida Solid and Hazardous Waste Regulation Handbook: Federal Insecticide, Fungicide, and Rodenticide Act (FIFRA) - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS, 2004)
The Federal Insecticide, Fungicide and Rodenticide Act (FIFRA) regulates pesticide sale, use, handling, and disposal. This is EDIS document FE446, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.